Cancellation of Marriage Due to Apostasy in Islamic Law and Human Rights: A Comparative Analysis of Indonesia and Malaysia - Sholehudin, Miftahus; Fadli, Moh; Sulistyarini, Rachmi; Djumikasih, Djumikasih (De Jure: Jurnal Hukum dan Syari'ah, 2025)
The issue of apostasy, especially the annulment of marriage on the grounds of apostasy, is a highly intricate and contentious issue at the intersection of Islamic law and human rights. This article seeks to undertake a critical comparative analysis of the legal frameworks, jurisprudence, and practical applications surrounding this issue within Indonesia and Malaysia—two prominent Muslim-majority countries. Through in-depth insight into the relevant laws and court cases with scholarly literature reviews, this paper examines the different approaches taken by these countries and the deeply entrenched challenges in resolving the principles of Islamic legal doctrine with the main tenets of international human rights. This examination requires treading the line carefully, as religious traditions and individual freedoms clash. An inclusive and balanced dialogue can be done to further the protection of human rights and respect the rich tapestry of religious and cultural perspectives. Indeed, the proper application of Islamic law can be viewed as a fundamental human right since the freedom to practice one’s faith is part and parcel of the core tenets of international human rights standards. It is in a holistic approach—one that respects both Islamic legal principles and universal human rights—that apparent tensions can be resolved and fair treatment can be ensured for everyone. Moreover, the Islamic jurisprudents take the invalidation of marriage by way of apostasy as unanimous since it is a permissible action in case of a defect or some damage in the marriage. However, clear and specific regulations are urgently needed with a view to legal certainty and unity within the community.